Determinación de parámetros tecnológicos para la consevación de inchicapi liofilizado - Coral Sanchez, Henry Paulo (2015)
The aim of this study was to develop and preserve the inchicapi by lyophilization method to do the organoleptic characteristics, proximate analysis and microbiological analyzes. The sequence of operations was: reception of raw materials , sorting and grading , heavy, washed and disinfected , liquid , frozen at a temperatura of -21ºC for 24 hours , freeze-dried , packaged and stored . To obtain the lyophilized inchicapi , they worked with pressure ( 0.05 mbar , 0.1 mbar and 0.16mbar ) and thicknesses (8mm y1 Omm ) subsequently underwent sensory evaluation to determine the best combination treatment thickness with pressure, giving the best result of O .16 mbar pressure and 1 O mm thickness . Product obtained low this modality presentad the following characterization: the first day: Dampness: 3.05 %; Fat: 40.5 %; Fiber: 5.1 %; Ash: 1.4 %; Protein: 22.6 %; Carbohydrates: 30.4 %; in Energy: 576.5 Kcal .two weeks later it was obtained: Dampness: 3.67 %; Fat: 38.5 %; Fiber: 6.5 %; Ash: 1.2 %; Protein: 21.5 %; Carbohydrates: 32.3 %; in Energy: 561.7 Kcal. Finally to one month later it was obtained: Dampness: 5.13 %; Fat: 39.0 %; Fiber: 7.3 %; Ash: 2.82 %; Protein: 21.42 %; Carbohydrates: 29.46 % and in Energy: 554.5 Kcal; demonstrating a good nourishing quality and guarantee of stability of the product. Regarding the safety of the lyophilized inchicapi, we can infer that it is a product with presence of microorganisms found below the standards allowed by Peruvian national standards